Comparative analysis of oxidative metabolism indicators at acute alcohol and acute surrogate alcohol intoxication - I. V. Beynikova; V. A. Snytina; L. E. Muravlyova; V. B. Molotov-Luchanskiy; R. E. Bakirova; D. A. Klyuev; L. B. Zhanbyrsheeva (Acta Biomedica Scientifica, 2016)
High level of population alcoholization is the cause of many cases of acute alcohol and alcoholic surrogate intoxication. The number of alcohol intoxication cases in Kazakhstan in 2014 amounted to 13891 (80.3 per 100 000 people), the number of fatal intoxication cases amounted to 882 (5.1 per 100 000 people). The problem of alcoholization in Russia remains urgent as well: according to the statistics of 2014,152 551 cases of acute intoxication of chemical etiology were registered, 33.9 % of cases occurred due to alcohol intoxication. Alcoholic beverages in the course of their biotransformation to acetic acid can form oxygen free radicals in particular superoxide anion as a byproduct of acetic aldehyde oxidation reaction. Studies on oxidative metabolism of ethanol intoxication are currently being conducted. At the same time, the state of oxidative metabolism during alcoholic surrogate intoxication was not practically investigated. Evaluation of oxidative metabolism depending on the severity of alcohol or its surrogate intoxication is of special interest. The aim was to compare oxidative metabolism indicators among patients with acute alcohol and alcoholic surrogate intoxication of different severity. The object of the study was blood of 62 people with diagnosed moderate or severe degrees of acute alcohol and alcoholic surrogate intoxication. Indicators of oxidative metabolism in erythrocytes and blood plasma were estimated. Significant differences were found in product concentration of protein oxidation containing bityrosine crosslinks in blood plasma under increase of alcohol intoxication degree.